Silencing miR-150 Ameliorates Experimental Autoimmune Encephalomyelitis - Hu, Zhaolan; Cui, Yanhui; Qiao, Xiaoqing; He, Xinwen; Li, Fang; Luo, Cong; Wang, Shuang; Li, Changqi; Dai, Ruping (Frontiers in Neuroscience, 2018)
MiR-150 regulates maturation and differentiation of T cells but how it functions in multiple sclerosis (MS) is unclear. In miR-150 knockout (KO) mice, we examined the effect of miR-150 deletion on disease severity of experimental autoimmune encephalomyelitis (EAE), an animal model of MS. After deleting miR-150, EAE disease severity was reduced according to clinical score. Histological staining and MBP immunofluorescence staining revealed that miR-150 deletion limited the extent of inflammatory demyelination and axonal damage in the spinal cord. Flow cytometry showed that CD3+, CD4+, and CD8+ T cells were increased in WT-EAE mice, but miR-150 deletion significantly reversed EAE-mediated up-regulation of CD3+, CD4+, and CD8+ T cells and down-regulation of CD19+ B cells. In addition, miR-150 deletion reduced the mRNA expression of IL-1β, IL-6, IL-17, and TNF-α in spleen and spinal cord after EAE induction. Thus, miR-150 deletion reduces EAE severity and demyelination, probably through inhibiting the activated immune response and the inflammation in the central nervous system.